Chronic Microvascular Complications in Sulfonylureas-Treated Diabetic Patients: Correlations with Glycemic Control, Risk Factors and Duration of the Disease - Luminita-Georgeta Confederat; Roxana Stefan; Mihaela-Iustina Condurache; Oana-Maria Dragostin (Clinics and Practice)
Background: Diabetes has become one of the most challenging public health problems due to the alarming increase in prevalence and the morbidity and mortality attributed to its acute and chronic complications. Objective: This study aimed to investigate the development of chronic microvascular complications in sulfonylureas-treated diabetic patients and their correlations with glycemic control, risk factors and duration of the disease. Methods: This study included 200 patients that presented to “Providența” Medical Center, Iași. The information was obtained in a retrospective manner based on the observation sheets of the patients. A database was created, analyzed and statistically processed using the Microsoft Excel software (Version 15) and the chi-square test of independence. Results: The prevalence of diabetic polyneuropathy was 33.5%, while diabetic retinopathy was found in 27% of cases. For diabetic polyneuropathy, the results of the statistical analysis demonstrated a statistically significant dependence of the risk factors hyperlipidemia (significance level = 0.01) and overweight/obesity (significance level = 0.05). For diabetic retinopathy, the results demonstrated a statistically significant dependence of the risk factors hypertension (significance level = 0.05) and hyperlipidemia (significance level = 0.01). Conclusions: The present study reveals a strong correlation between the presence of risk factors and the development of microvascular complications of diabetes.